Comparative Evaluation of Modern Inhalation Anesthetics in Carotid Endarterectomy - V. A. Aliev; A. G. Yavorovskii; A. A. Shaposhnikov; I. Zh. Loriya; M. S. Vetsheva (Общая реаниматология, 2019)
The purpose of the study was to compare the possibility of rapid activation of elderly patients after carotid endarterectomy performed under sevoflurane- or desflurane-based anesthesia. Materials and methods. 67 patients aged 75 to 89 years divided into two groups were examined. To maintain anesthesia, desflurane was used in the 1st group and sevoflurane was employed in the 2nd group. Results. Patients from the group receiving desflurane, experienced decreased ability to take a sip of water and to hold oneself in a sitting position, and were characterized by decreased time before the tracheal extubation. Conclusion. Desflurane-based anesthesia provided faster awakening and activation of elderly patients after carotid endarterectomy than the anesthesia with sevoflurane, which allowed to implement the fast-track recovery protocol. In addition, the desflurane-based anesthesia provided excellent manageability and less negative impact on the hemodynamics (within the drug concentration range of up to 1.3 MAC).